2018
DOI: 10.1111/gcb.14066
|View full text |Cite
|
Sign up to set email alerts
|

Major limitations to achieving “4 per 1000” increases in soil organic carbon stock in temperate regions: Evidence from long‐term experiments at Rothamsted Research, United Kingdom

Abstract: We evaluated the “4 per 1000” initiative for increasing soil organic carbon (SOC) by analysing rates of SOC increase in treatments in 16 long‐term experiments in southeast United Kingdom. The initiative sets a goal for SOC stock to increase by 4‰ per year in the 0–40 cm soil depth, continued over 20 years. Our experiments, on three soil types, provided 114 treatment comparisons over 7–157 years. Treatments included organic additions (incorporated by inversion ploughing), N fertilizers, introducing pasture leys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
192
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(244 citation statements)
references
References 63 publications
11
192
2
1
Order By: Relevance
“…Our study represents one of few long-term efforts to track soil carbon changes throughout both the surface and subsoil layers in (Périé & Ouimet, 2008). Poulton et al (2018) also observed declines in bulk density in longterm cropping system experiments.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Our study represents one of few long-term efforts to track soil carbon changes throughout both the surface and subsoil layers in (Périé & Ouimet, 2008). Poulton et al (2018) also observed declines in bulk density in longterm cropping system experiments.…”
Section: Discussionmentioning
confidence: 72%
“…Bulk density likely declined in the surface layers of most systems due to the cumulative addition of organic matter, which built up as bulky or particulate organic matter; others have observed an inverse relationship between soil organic matter and bulk density (Périé & Ouimet, ). Poulton et al () also observed declines in bulk density in long‐term cropping system experiments.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The international 4‰ initiative, launched at the COP‐21 conference in Paris (Minasny et al ., ) as a means to combat increasing atmospheric concentrations of CO 2 , aims to increase C content in the top 40 cm of the soil by 0.4% annually by improved land management and land‐use change. Although the quantitative realism of this initiative has been questioned (Poulton et al ., ), increased soil C storage will counteract, at least for a period, the increase in atmospheric CO 2 concentration. One option to store more C in soil is to revert degraded and arable lands with small C content and limited productivity to permanently vegetated soils such as semi‐natural grasslands (Powlson et al ., ).…”
Section: Introductionmentioning
confidence: 99%